PERBEDAAN PENGETAHUAN TENTANG KARIES GIGI PADAANAK SEKOLAH DASAR GMIM 20 (kelas 4-5 ) DAN YAYASAN Ds.A.Z.R.WENAS SEKOLAH DASAR GMIM MALALAYANG ( kelas 4-5 ) KOTA MANADO - Ni Made Yuliana; Jeineke E. Ratuela; Yenny Lisbeth Siahaan (Poltekkes Kemenkes Medan, 2023)
Knowledge is the result of knowing one's object through the senses it has (eyes, nose, ears, and so on). Most of a person's knowledge is obtained through the sense of hearing (ears), and the sense of sight (eyes). A person's knowledge of objects has different intensities or levels. The purpose of this study was to determine the differences in knowledge of dental caries in elementary school students GMIM 20 (grades 4-5) and the Ds.A.Z.R Foundation. Wenas Elementary School GMIM Malalayang Manado City. This type of research uses an analytical survey research method that is a comparative study with a cross sectional approach. The sample used is 89 respondents. Consisting of 46 respondents at GMIM 20 Elementary School and 43 respondents at Ds.A.Z.R. Elementary School. Wenas. This research instrument uses a questionnaire containing questions. The data obtained were tabulated and presented in the form of a frequency distribution table and analysis test using independent t-test.From the test results using the independent t-test that the p value of sig. (2-tailed) = 0.000 < = 0.05 indicates that there is a significant difference, thus H0 is accepted H1 is rejected so that it can be concluded that there is a difference in the knowledge of grade 4 and 5 students between GMIM 20 Elementary School and Ds.A.Z.R. Foundation Elementary School. Wenas city of Manado.